2021
DOI: 10.1186/s12871-021-01417-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Oxycodone versus morphine for analgesia after laparoscopic endometriosis resection

Abstract: Background The objective of this study was to compare the analgesic potency of oxycodone versus morphine after laparoscopic deep infiltrating endometriosis resection. Methods Fifty patients undergoing laparoscopic deep infiltrating endometriosis resection were randomized to receive oxycodone or morphine intravenous-PCA after surgery. The primary outcome was opioid consumption during the 24 h after surgery. Secondary outcomes included time to first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Most importantly, the same analgesic effect can be achieved with a smaller dose ( 12 ). A clinical study found that morphine and oxycodone exhibited comparable efficacy in addressing skin and muscle pain, whereas oxycodone provided better analgesia for esophageal pain caused by thermal and electrical stimulation ( 13 ). In terms of acute pain efficacy, oxycodone is administered at doses less than morphine 2 h after abdominal surgery because it can rapidly cross the blood-brain barrier into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the same analgesic effect can be achieved with a smaller dose ( 12 ). A clinical study found that morphine and oxycodone exhibited comparable efficacy in addressing skin and muscle pain, whereas oxycodone provided better analgesia for esophageal pain caused by thermal and electrical stimulation ( 13 ). In terms of acute pain efficacy, oxycodone is administered at doses less than morphine 2 h after abdominal surgery because it can rapidly cross the blood-brain barrier into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…κ-opioid receptor plays an important role in the mediation of visceral pain (6). Oxycodone, a dual agonist of μ and κ receptors (14), has been shown to provide effective analgesia for acute postoperative pain (15,16), especially visceral pain. However, the safe and effective dose of oxycodone in PCIA following laparoscopic surgery for gastrointestinal cancer in elderly patients has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for high postoperative pain scores have been established [6,7]. Nearly all types of surgery that yield high postoperative pain can be treated with IV-PCA in the acute phase; examples of such surgeries include spine and other complex orthopedic surgeries, such as knee and hip [15], open abdominal [16] and non-ambulatory laparoscopic surgery [17]; and thoracic [18], major cervicofacial and reconstruction surgeries [19], including breast surgeries [20]. In addition to initial severe postoperative pain, some surgeries can also yield chronic postoperative pain such as cardiac [21], knee [22] shoulder [23] and hip pain [24].…”
Section: Indications and Benefits Of Pcamentioning
confidence: 99%